2023
DOI: 10.1007/s10841-023-00493-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of Orthoptera in vineyards to organic farming, pesticide reduction, and landscape heterogeneity

Marvin Kaczmarek,
Melanie Gillich,
Martin H. Entling
et al.

Abstract: Conservation measures such as those under the European Green Deal aim to counteract the biodiversity loss by increasing the share of organic farming and reducing pesticide use, as well as increasing the proportion of semi-natural habitats (SNH) in agricultural landscapes. Given the large environmental impacts of agriculture, it is important to thoroughly understand effects of such measures on organisms to provide evidence-based and effective implications for conservation. In this study, we analysed how vineyar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…While some studies have reported strong positive effects of semi-natural habitats on populations of insects, spiders, and birds, the impact on Orthoptera was found to be weak in vineyards of the region Palatinate in southwestern Germany [55]. Different taxa respond differently to the same vineyard management approaches, and therefore, they should be adapted to each specific context [41].…”
Section: Semi-natural Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have reported strong positive effects of semi-natural habitats on populations of insects, spiders, and birds, the impact on Orthoptera was found to be weak in vineyards of the region Palatinate in southwestern Germany [55]. Different taxa respond differently to the same vineyard management approaches, and therefore, they should be adapted to each specific context [41].…”
Section: Semi-natural Habitatsmentioning
confidence: 99%
“…VineyardsMaintenance of semi-natural habitat, including wildflower strips of field paths and weedy areas  Biological control of pests (tortricid moths and grape berry moths, mealybugs, mites/and phylloxera) Enhance the abundance and diversity of predatory arthropods in vineyards[42,[50][51][52] Maintenance of semi-natural habitat, including woody elements Abundance and species richness of cavitynesting bees and breeding birds that provide relevant ecosystem services[53][54][55] …”
mentioning
confidence: 99%